ANALISIS NILAI-NILAI AKHLAK DALAM KITAB 'AQIDATUL 'AWAM KARYA SYAIKH AHMAD MARZUQI - Nur Anisah; Abdullah Idi; Mukti Ali; Aristophan Firdaus; Sukirman Sukirman (PAI RAFAH, 2023)
In this research entitled "Analysis of Moral Values in the Book of 'Aqidatul 'Awam by Shaykh Ahmad Marzuqi". Which aims to find out what moral values we can know in the book. referring to the book 'Aqidatul 'Awam, because the book discusses the basic principles of monotheism for Muslims, and the words are easily understood by lay people. And also this book has relatively little lafadz because the book is also thin, but it has a lot of meaning and a very broad scope. The tawhid that the author means is the tawhid that believes in one God. By analyzing the book, researchers can find out what moral values are contained in the book. The type of research used is literature (Library Research) using a qualitative approach. The primary data source in this research is the Book of 'Aqidatul 'Awam by Shaykh Ahmad Marzuqi. The data collection technique is by going to the library to find reading sources obtained from journals, books, and so on. The data analysis of this research is content analysis. content analysis. The results of the research that has been carried out from the book studied are that there are several moral values, namely morals to Allah, morals to prophets and messengers, and morals to angels.